An investigation on the ship rudder with different control system - (:unkn) unknown (My University, 2010)
In this study, it has been searched that how control changes with different controls by discussing technical properties of a chemical tanker. Nowadays numerous control methods have been developed on this purpose. In this study, controlling of drift and roll motions of chemical tankers has been done by using proportional, integral, derivative and fuzzy logic methods. In performed simulations, second order Nomoto model has been used for drift motion that has one degree of freedom.